Research on the Operational Parameters and Performance of Key Components of an Industrial Hemp Harvester and Drier - Chao Feng; Changxi Liu; Bosheng Wang; Hang Shi; Hao Sun; Yufei Li; Jun Hu (Agriculture)
Industrial hemp has significant utilization value, and China is the largest producer of industrial hemp in the world, primarily growing hemp for fiber. Heilongjiang Province is the largest area of hemp fiber cultivation in China. In response to issues such as inconsistent operating standards, low efficiency, and poor harvesting quality of industrial hemp harvesters in China, this study integrates the mechanical properties of the “Hanma 5” hemp stalk and applies cutting platform design theory to analyze and optimize the key components of existing hemp harvesters, aiming to obtain optimal operational parameters. First, by analyzing the motion laws of the cutting blade and the regression equations of shear power consumption and shear force, the relationship between cutting speed and time is established, and the cutting and conveying parameter ranges are derived, providing the basis for subsequent simulation analysis and field validation. Next, dynamic simulation analysis of the key components of the domestic 4GM-2.2 industrial hemp harvester for fiber is conducted using ADAMS and Workbench. The conveyor speed values and corresponding chain drive combinations under different conveyor speed ratios are obtained. Field experiments validated the optimal combination of key operational parameters for the industrial hemp harvester as follows: forward speed of 2.1 m/s, cutting speed of 2.5 m/s, conveyor speed ratio of 2.2, coefficient of variation for the laying angle of 6.88%, coefficient of variation for the laying thickness of 4.11%, and cutting height of 10.4 cm. Under the optimal operational parameter combination, the re-cut rate was 8.4%, with no missed cutting observed. This paper provides technical references for exploring the optimal operational parameters of industrial hemp harvesters for fiber to achieve high-quality harvesting operations.